A capoeira como escola de ofício - Gomes da Silva, Mellissa Fernanda; Neto, Samuel de Souza; Benites, Larissa Cerignoni (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
The purpose of this paper is to provide an in-depth look at the origins of the capoeira, as well as the occupation school, aiming to structure a work in the historic-bibliographic perspective which allows elucidating this relation with the occupation school, since this beging its origins until nowadays. It is a descriptive study, using the source documentary collection of data. Among the results it was observed that the capoeira it was not considered a ocupation (it was rather forbidden) but a "subsistence system", being transmitted from one generation to the other orally. The paths that the capoeira has walked through and, under certain circumstance, has draw for itself, make it a occupation school, such as in the relationship master-apprentice which lasts until the present moment. We are able to conclude that the capoeira as corporation and occupation school are realities lived due to its structure and function, both present in the contemporary world.

Este estudo teve por objetivo aprofundar os conhecimentos acerca da origem da capoeira, bem como das escolas de ofício, buscando estruturar um trabalho na perspectiva histórico-bibliográfico que permitisse elucidar a sua relação com a escola de ofício, desde o seu início até os dias atuais. Trata-se de um estudo descritivo, tendo na fonte documental a sua coleta de dados. Entre os resultados obtidos observou-se que a capoeira não era considerada um ofício (ao contrário era proibida), mas um “sistema de subsistência”, sendo transmitida de geração a geração oralmente. Os rumos que a própria capoeira trilhou, e de certa forma traçou para si, a tornam uma escola de ofício, como na relação mestre-aprendiz que perdura até o momento. Podemos concluir que a capoeira como corporação e escola de ofício são realidades vividas devido a sua estruturação e funcionamento, presentes no mundo contemporâneo.
The Capoeira as Ocupation School
Keywords: Capoeira; Ocupation School; Ocupation Corporation